Effect of Graft Choice on the 6 Year Outcome of Revision Anterior Cruciate Ligament Reconstruction in the Multicenter ACL Revision Study (MARS) Cohort. Issue 7 (29th July 2019) - Group, Mars; Wright, Rick W.
Objectives: Most surgeons believe that graft choice for anterior cruciate ligament (ACL) reconstruction is an important factor related to outcome. The purpose of this study was to determine if revision ACL graft choice predicts outcomes related to sports function, activity level, OA symptoms, graft re-rupture, and reoperation at six years following revision reconstruction. We hypothesized that autograft use would result in increased sports function, increased activity level, and decreased OA symptoms (as measured by validated patient reported outcome instruments). Additionally, we hypothesized that autograft use would result in decreased graft failure and reoperation rate 6 years following revision ACL reconstruction. Methods: Revision ACL reconstruction patients were identified and prospectively enrolled by 83 surgeons over 52 sites. Data collected included baseline demographics, surgical technique and pathology, and a series of validated patient reported outcome instruments (IKDC, KOOS, WOMAC, and Marx activity rating score). Patients were followed up for 6 years, and asked to complete the identical set of outcome instruments. Incidence of additional surgery and re-operation due to graft failure were also recorded. Multivariate regression models were used to determine the predictors (risk factors) of IKDC, KOOS, WOMAC, Marx scores, graft re-rupture, and re-operation rate at 6 years following revision surgery. Results: 1234 patients were successfully enrolled with 716 (58%) males. Median age was 26. In 87% this was their first revision. 367 (30%) were undergoing revision by the surgeon that had performed the previous reconstruction. 598 (48%) underwent revision reconstruction utilizing an autograft, 599 (49%) allograft, and 37 (3%) both autograft and allograft. Median time since their last ACL reconstruction was 3.4 years. Questionnaire follow-up was obtained on 810 subjects (65%), while phone follow-up was obtained on 949 subjects (76%). The IKDC, KOOS, and WOMAC scores (with the exception of the WOMAC stiffness subscale) all significantly improved at the 6-year follow-up time point (p<0.001). Contrary to the IKDC, KOOS, and WOMAC scores, the 6-year MARX activity scale demonstrated a significant decrease from the initial score at enrollment (p<0.001). Graft choice proved to be a significant predictor of 6-year Marx activity level scores (p=0.005). Specifically, the use of an autograft for revision reconstruction predicted improved activity levels [Odds Ratio (OR) = 1.54; 95% confidence intervals (CI) = 1.14, 2.04]. Graft choice proved to be a significant predictor of 6-year IKDC scores (p=0.018), in that soft tissue grafts predicted higher 6-year IKDC scores [OR = 1.62; 95% confidence intervals (CI) = 1.09, 2.414]. For the KOOS subscales, graft choice did not predict outcome score. Graft re-rupture was reported in 55/949 (5.8%) of patients by their 6-year follow-up: 37 allografts, 16 autografts, and 2 allograft + autograft. Use of an autograft for revision resulted in patients 6.04 times less likely to sustain a subsequent graft rupture than if an allograft was utilized (p=0.009; 95% CI=1.57, 23.2). Conclusion: Improved sports function and patient reported outcome measures are obtained when an autograft is utilized. Additionally, autograft type shows a decreased risk in graft re-rupture at six years follow-up. Surgeon education regarding the findings in this study can result in potentially improved revision ACLR results for our patients.